PERMAINAN LOMTUKI SEBAGAI INOVASI PEMBELAJARAN NUMERASI AWAL ANAK USIA DINI - Eka Fitriani Sangadah; Aprilia Wahyuning Fitri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low ability to recognize numbers 1-10 in 4-5 year-old children at Muslimat NU 32 Nurul Hikmah Kindergarten is the background to this research, which is triggered by a reliance on lecture methods and static worksheets. The focus of the research problem is to develop innovative early numeracy learning through motor games. This study used the Research and Development (R&D) method with a 4D model, which includes the define, design, and develop stages. Data collection instruments included observation, interviews, and a validation questionnaire. The results of content validation using the Aiken's V formula showed a value between 0.05 and 1.00, categorizing this media as highly valid. In the limited trial phase involving 22 children and 4 teachers, quantitative data obtained in the form of a feasibility score of 4.8 and a practicality score of 4.8 on a scale of 5.0, thus categorizing the product as highly feasible and practical. The findings indicate that the Lomtuki game is effective in creating a fun, active learning atmosphere by integrating physical activity and number concepts in a concrete manner. The main conclusion of the study confirms that the Lomtuki game is an alternative, innovative learning medium empirically proven to optimize early cognitive and numeracy development in early childhood through systematic motor coordination. The integration of bright visuals and social interaction during play is key to successfully fostering enthusiasm for independent learning, which impacts cognitive readiness for the elementary school transition.